2023
DOI: 10.14309/ajg.0000000000002526
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-Related Changes in Incidence and Mortality Rates of Gastrointestinal Cancers During 2020

Caitlin C. Murphy,
Anna Tavakkoli,
Sachin Wani
et al.

Abstract: Background: COVID-19 disrupted cancer-related care in early 2020. Methods: We used population-based cancer registry data to estimate incidence and mortality rates of GI cancers between 2016 and 2020. Results: Incidence rates were unchanged from 2016 to 2019 but decreased in 2020, with the largest declines for colorectal cancer (RR 0.88; 95%CI 0.87, 0.90) and hepatocellular carcinoma (RR 0.85; 95%CI 0.82, 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Digestive system cancers pose a significant global health challenge due to their high incidence and mortality rates [1][2][3][4][5]. Epidemiological analyses demonstrated that digestive system cancers, encompassing malignancies of the oesophagus, stomach, liver, pancreas, colon and rectum, significantly contribute to the overall health burden worldwide [6][7][8]. Recent advancements in endoscopic techniques and minimally invasive surgery have greatly improved the outcomes and quality of life for individuals diagnosed with early-stage digestive system cancers [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Digestive system cancers pose a significant global health challenge due to their high incidence and mortality rates [1][2][3][4][5]. Epidemiological analyses demonstrated that digestive system cancers, encompassing malignancies of the oesophagus, stomach, liver, pancreas, colon and rectum, significantly contribute to the overall health burden worldwide [6][7][8]. Recent advancements in endoscopic techniques and minimally invasive surgery have greatly improved the outcomes and quality of life for individuals diagnosed with early-stage digestive system cancers [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%